Evaluation of lightning current parameters using measured lightning induced voltage on distribution power lines - Izadi M.; Kadir M.Z.A.A.; Osman M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electromagnetic fields; Parameter estimation; Channel base current; Electromagnetic field components; Lightning current parameters; Lightning induced voltage; Lightning location; Lightning location systems; Overhead distribution line; Performance of algorithm; Lightning